Restrictions on Individual Land Ownership for Residential Purposed in Indonesia: A Proposed Solution - Febri Jaya; Lu Sudirman; Nurlaily Nurlaily; David Tan (CV. RADJA PUBLIKA, 2026)
The government has a responsibility to provide decent housing for all Indonesian people. The absence of legal regulations regarding the limitation of ownership of land rights for residential houses for individuals causes a person to freely and without limits buy a residential house. The purpose of housing purchases has shifted from the needs to be an investment does not protect the rights of all citizens to obtain a decent place to live in order to achieve prosperity and justice. To answer the problems in this research, the researcher uses a normative type of research with a legal approach to fill the lacuna of existing legal regulations in Indonesia since the object of the research is not yet legally regulated. The focus of attention on normative law as a practical science is to change the situation and offer solutions to concrete and potential social problems. The problems faced by each individual (especially people of the middle to lower income) to get a decent house are of course the responsibility of the government. This situation is constitutionally mandated under the 1945 Constitution of the Republic of Indonesia. The answers to the problems, the researcher will approach the study by utilizing the approaches, in particular the Welfare State Theory of John Rawls, and the Law Development Theory of Mochtar Kusumaatmadja. As a conclusion, the solution proposed by the researcher is the application of the triple check system in the preparation of Government Regulations regarding the limitation of control over the land rights for residential houses for individuals in Indonesia.